The manual of seed saving : harvesting, storing, and sowing techniques for vegetables, herbs, and fruits - Heistinger, Andrea (Timber Press, 2013)
This authoritative guide brings together the experience of experts in the field who have found, through careful trialing, how to reliably maximize seed quality and yield for more than 100 crop plants. Clear information on such critical issues as pollination, isolation distances, cultivation, harvest, storage, and pests and diseases is provided. The Manual of Seed Saving is an essential reference for all food producers from vegetable growers to small-scale farmers.--COVER.